Effect of Hospital Safety Net Burden on Survival for Patients With Sinonasal Squamous Cell Carcinoma. (28th January 2023) - Tseng, Christopher C.; Gao, Jeff; Barinsky, Gregory L.; Fang, Christina H.; Grube, Jordon G.; Patel, Prayag; Hsueh, Wayne D.; Eloy, Jean Anderson
Abstract: Objective: To examine factors associated with hospital safety net burden and its impact on survival for patients with sinonasal squamous cell carcinoma (SNSCC). Study Design: Retrospective database study. Setting: National Cancer Database from 2004 to 2016. Methods: SNSCC cases were identified in the National Cancer Database. Hospital safety net burden was defined by percentage of uninsured/Medicaid patients treated, namely ≤25% for low‐burden hospitals, 26% to 75% for medium‐burden hospitals, and >75% for high‐burden hospitals (HBHs). Univariate and multivariate analyses were used to investigate patient demographics, clinical characteristics, and overall survival. Results: An overall 6556 SNSCC cases were identified, with 1807 (27.6%) patients treated at low‐burden hospitals, 3314 (50.5%) at medium‐burden hospitals, and 1435 (21.9%) at HBHs. On multivariate analysis, Black race (odds ratio [OR], 1.39; 95% CI, 1.028‐1.868), maxillary sinus primary site (OR, 1.31; 95% CI, 1.036‐1.643), treatment at an academic/research program (OR, 20.63; 95% CI, 8.868‐47.980), and treatment at a higher‐volume facility ( P < .001) resulted in increased odds of being treated at HBHs. Patients with grade III/IV tumor (OR, 0.70; 95% CI, 0.513‐0.949), higher income ( P < .05), or treatment modalities other than surgery alone ( P < .05) had lower odds. Survival analysis showed that hospital safety net burden status was not significantly associated with overall survival (log‐rank P = .727). Conclusion: In patients with SNSCC, certain clinicopathologic factors, including Black race, lower income, treatment at an academic/research program, and treatment at facilities in the West region, were associated with treatment at HBHs. Hospital safety net burden status was not associated with differences in overall survival. Level of evidence: 4.